Intelligent Synthesis of Cyber-Resilient Network Structures: Methods, Experiments, and Architecture Implementation - Pavlenko, E. Yu (Automatic control and computer sciences, 2024)
This paper studies issues related to the implementation of intellectual synthesis of cyber-resilient structures. Methods are proposed that implement synthesis both at the stage of designing the network structure and at the stage of its recovery during a cyberattack or failure. The experimental results confirming the efficiency of the proposed methods are presented. The architecture of the system for detecting cyberattacks and intellectual synthesis of cyber-resilient network structures is described.